Cloud Workflow Modeling Based on Extended Proclets Framework - Huang, Hua; Peng, Rong; Feng, Zaiwen (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
How to promote common process fragments reuse, how to accelerate business process customization process for multiple tenants and how to model interactions between different tenants' business processes while protecting their privacy, are the main research focuses of existing cloud workflow modeling approaches. This paper proposes a cloud workflow modeling approach based on an extended proclets framework which has the following advantages: 1) provides a hierarchical management mechanism to isolate the private data of each tenant’s business process; 2) adopts two-level-channel transmission protocol to explicitly model interaction between different tenants' business processes. To exactly describe and understand the modeling approach, the formal definition and construction procedure of cloud workflow model based on extended proclets are presented. At last, a case study is carried out to illustrate its modeling capability and feasibility, and to evaluate the applying effect of our modeling approach, the run effect of a cloud workflow system developed by adopting our proposed modeling approach is evaluated through three indexes: communication error rate, data leakage rate and user satisfaction.